OPTIMIZACIÓN DEL DISEÑO DE UN ROOFTOP TENT DE PRODUCCIÓN NACIONAL - Ojeda Barrionuevo, Bryan David (2024)
The research project focuses on optimizing the design of roof tents for off-road activities in Ecuador, taking advantage of the local industry due to the lack of industrialization of these products in the country, where they are currently only imported. For optimization, guiding steps were developed to improve the design, focusing on performance, durability and user experience. The main off-road activities and requirements for installing and constructing a rooftop tent were investigated. In addition, features and construction systems of existing tents were analyzed to identify design improvements and relevant accessories. The analysis included both literature and field research. As a result, a table was created that specifies the key characteristics of current tents, facilitating the understanding of technical and production factors, and a series of guiding steps were developed that facilitate the optimization of rooftop tent construction. This process determined that optimizing rooftop tent design not only improves the performance and durability of the tents, but also makes them more attractive and competitive for campers and off-road enthusiasts.